Case study of wind-induced performance and equivalent static wind loads of large-span openable truss structures. (June 2022) - Ma, Ting-ting; Zhao, Lin; Ji, Teng-fei; Tang, Te
Abstract: Wind load is one of the governing design loads for large-span structures. The wind-resistant design of openable structures is more complicated due to the variability in aerodynamic configuration and structural dynamic characteristics. Taking a large-span truss roof with rotatable roof structures as a case study, the pressure measurement wind-tunnel test, finite element modeling, dynamic response analysis, and aeroelastic model test were carried out for evaluating the wind-induced response and equivalent static wind loads (ESWLs) of the roof structure under both closed and open working states. Four types of ESWL calculation methods were analyzed and compared with each other, with the member stress as the equivalent target. The results show that the cantilever structures of the open roof state induce a significant drop in structural fundamental frequency, and the wind-induced response becomes much larger than that of the closed one under the same oncoming flow. The background response dominates the wind-induced vibration under the closed roof state, while for the open state, the results are the opposite. The displacement-related wind-induced vibration factor method for ESWL calculation presents best agreement with the transient analysis results from the perspective of overall stress equivalence of all key members for design, and therefore is recommended for the wind load equivalence of the openable roof structure in this study. Additionally, some other equivalent methods like the target-reduced universal ESWL method and the single-stress-targeted GLF method may serve as a supplement for stress equivalence of local members with large stress deviations. Highlights: Dynamic and aerodynamic characteristics of an openable truss roof were investigated. Analytical wind-induced dynamic response was verified by a simplified aeroelastic model test. Four types of ESWL calculation methods were investigated towards the openable roof. Wind-induced vibration factor method is effective for ESWL estimation of truss roofs.